REVIEW ON THE ABSORPTION OF ELEMENTS OF THE GOVERNMENT INTERNAL CONTROL SYSTEM (SPIP) IN THE ENVIRONMENTAL CONTROL UNIT AT THE MINISTRY OF PUBLIC WORKS AND PUBLIC HOUSING (PUPR) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to review the application of elements of the Government Internal Control System (SPIP), particularly in the element of the control environment at the Ministry of Public Works and Public Housing (PUPR). The method used in this study is a survey that is classified in the type of quantitative descriptive research. Data collection by distributing questionnaires in 8 work units of the Ministry of Public Works and Public Housing (PUPR) with 76 respondents. Data analysis uses descriptive statistics. The results of data processing concluded that the enforcement of integrity and ethical values ​​and the embodiment of the role of the Government Internal Oversight Apparatus (APIP) had been carried out effectively and adequately within the Ministry of Public Works and Public Housing. on aspects of commitment to competence, conducive leadership, establishment of organizational structures in accordance with needs, delegation of appropriate authority and responsibilities, preparation and application of sound policies regarding management / guidance of Human Resources and good working relationships with relevant government agencies carried out with adequate.